Pengaruh Appraisal, Pengembangan Profesional, dan Kesehatan Mental terhadap Kinerja Guru di Sekolah Menengah Pertama XYZ Jakarta [The Influence of Appraisal, Professional Development, and Mental Health on Teacher Performance at XYZ Junior High School, Jakarta] - Setyanta, Bernadeta Ayu; Emeliana Makaria Tarigan; Yohanita Kristin Imawati (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2025)
This study aims to determine the influence of appraisal, professional development, and mental health on teacher performance at SMP XYZ Jakarta. The results showed that all three variables have an influence on teacher performance, with mental health as the most dominant factor. The effect of appraisal on teacher performance has a coefficient of determination (R²) of 5.5%, indicating a small but influential contribution to improving performance. Professional development contributed 7.7% to teacher performance, indicating the importance of training and competency development programs. Meanwhile, mental health made the largest contribution with a coefficient of determination of 63.8%, confirming that teachers' mental well-being is an important factor in supporting optimal performance. Based on these findings, it is recommended that schools improve the effectiveness of the appraisal system, strengthen professional development programs, and pay more attention to the mental health aspect of teachers. These strategies are expected to significantly and sustainably improve teacher performance.